Learning from experience: From case-based teaching to experience-based learning. Issue 1 (March 2017) - van der Steen, Martijn; Van Twist, Mark; Frissen, Paul
Senior-level civil servants can learn a lot from methods such as theory-lectures and case-teaching, but there is another resource of knowledge and insight that can be utilized more for teaching public administration: the professional experience of participants in training programmes. This paper argues that it is possible to use the professional experience of participants in training programmes as didactical building blocks for training. This helps participants to overcome the divide between theory and practice, which is a recurring theme in the debate about how to design good education programmes for seasoned practitioners that work in the continuously developing 'real world' of public administration. However, apart from teaching there is yet another possibility to utilize the practical experience of participants in executive education. To further develop the field of public administration research it is possible to also use the professional practice that is opened up by education programmes as a basis for research . The classroom of public administrating training then also becomes a space for interpretative research in public administration. Education and research are often considered worlds apart that only come together when theory from research is taught in education. In this paper, we present a format that intertwines education and research, by using the professional experiences of practitioners as the building block for training and for interpretative public administration research. In doing so, this didactical format, which we call learning atelier, turns the classroom in to a place for learning, a place of practice and a place for research.